2022
DOI: 10.3389/fonc.2022.1010088
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of radiotherapy in breast cancer patients underwent immediate reconstruction after mastectomy

Abstract: IntroductionIt is still unclear whether radiotherapy affects the long-term survival of breast cancer (BC) patients after immediate breast reconstruction (IBR). This study aims to evaluate the actual prognostic impact of radiotherapy on BC patients undergoing IBR, and to construct survival prediction models to predict the survival benefit of radiotherapy.MethodsData on eligible BC patients were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Competing risk models were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…While multiple studies have con rmed the bene cial effects of radiotherapy on overall survival (OS) in breast cancer patients 45 , others have suggested that its bene ts may be limited. For instance, Chua et al found that radiotherapy effectively reduced local-regional recurrences but not distant recurrences 46 .…”
Section: Resultsmentioning
confidence: 99%
“…While multiple studies have con rmed the bene cial effects of radiotherapy on overall survival (OS) in breast cancer patients 45 , others have suggested that its bene ts may be limited. For instance, Chua et al found that radiotherapy effectively reduced local-regional recurrences but not distant recurrences 46 .…”
Section: Resultsmentioning
confidence: 99%
“…These factors could potentially impact the survival outcomes of black patients after breast reconstruction. Radiation therapy may be associated with adverse events of breast reconstruction surgery, such as: reconstruction failure, capsular contracture, and overall complications [24][25][26] [27][28] [29][30] [31]. A retrospective study conducted on breast cancer patients demonstrated that radiotherapy had a positive impact on OS and BCSS in patients with N3 stage who underwent autologous breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is one of the most common malignancies in women, with 1.3 million cases diagnosed and 400,000 deaths worldwide each year [ 1 , 2 ]. The etiologies of BC are very complex, and its onset and therapeutic effect are related to a variety of factors, such as estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2), BRCA, and hormone levels [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%